Students’ Perceptions of Learning Management System in Teaching Mechanics During The Pandemic of COVID-19 - Suranti, Ni Made Yeni; Gunawan, Gunawan; Harjono, Ahmad; Imran, Imran (Indonesian Publication Center, 2020)
The learning management system is one of the inventions in information technology that is incorporated into education. A Learning management system (LMS) is an important solution to tracking and addressing the online learning needs of the students in the social distancing period. The ultimate goal of this research is to produce LMS devices on Mechanics material to improve mastery of concepts and creativity. In this article students’ responses or perceptions will be addressed after being handled with LMS devices in the process of learning. This study involves research and development using 4D models which include define, design, develop and disseminate. The results of this study are the results of the developmental testing phase. The instrument used was in the form of student response questionnaire in Likert scale. Students give positive responses to the use of LMS devices. Student responses are at intervals of 81% to 100%, with a very good category. Learning process can work well. Students can easily access learning resources to do exercises to improve learning outcomes. The LMS devices developed was effectively used during learning and became one of the innovative learning in the social distancing pandemic COVID-19 period.